Price level changes and the redistribution of nominal wealth across the euro area - Klaus Adam; Junyi Zhu (European Central Bank (ECB), 2015)
We show that unexpected price level movements generate sizable wealth redistribution in the Euro Area (EA), using sectoral accounts and newly available data from the Household Finance and Consumption Survey. The EA as a whole is a net loser of unexpected price level decreases, with Italy, Greece, Portugal and Spain losing most in per capita terms, and Belgium and Malta being net winners. Governments are net losers of deflation, while the household (HH) sector is a net winner in the EA as a whole. HHs in Belgium, Ireland, Malta and Germany experience the biggest per capita gains, while HHs in Finland and Spain turn out to be net losers. Considerable heterogeneity exists also within the HH sector: relatively young middle class HHs are net losers of deflation, while older and richer HHs are winners. As a result, wealth inequality in the EA increases with unexpected deflation, although in some countries (Austria, Germany and Malta) inequality decreases due to the presence of relatively few young borrowing HHs. We document that HHs inflation exposure varies systematically across countries, with HHs in high inflation EA countries holding systematically lower nominal exposures.
Keywords: E31; D31; D14; 330; euro area; household survey; price level; redistribution